Pengaruh Body Shaming dan Intensitas Interaksi Teman Sebaya terhadap Kepercayaan Diri Remaja Putri di Kecamatan Paninggaran Kabupaten Pekalongan - Khoirunisa, Novita (IAI Nasional Laa Roiba Bogor, 2024)
Self-confidence is confidence in the abilities possessed by individuals so that individuals are able to achieve what they want. Each individual has a different level of self-confidence, which is usually influenced by the extent of the acceptance of the surrounding environment to each individual.The purpose of this study was to empirically examine the effect of body shaming and the intensity of peer interaction on the self-confidence of young women in Paninggaran District, Pekalongan Regency. The sample in this study was 227 young women in Paninggaran District, Pekalongan Regency. This study uses a quantitative approach. The sampling technique used in this research is incidental sampling technique. The measurement tools for this study consisted of a body shaming scale, a scale of peer interaction intensity and a self-confidence scale. The data analysis method in this study uses multiple linear regression analysis. Based on the results of the study, it shows that body shaming has a significant effect on self-confidence with a significance value of 0.000 <0.05. Meanwhile, the intensity of peer interaction has a significant effect on self-confidence with a significance value of 0.000 <0.05. Then there is the effect of body shaming and the intensity of peer interaction on the self-confidence of young women (adj r square 0.455, p = 0.000 <0.05). That is, the higher the body shaming and the intensity of peer interaction, the lower the self-confidence and vice versa.